Improving Student Learning Outcomes through the Quantum Teaching Learning Model on Worship Material and Its Characteristics at MA Guppi Rannaloe - Syam, Khaeruddin; Jumriani (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine how the implementation of the Quantum Teaching learning model can improve students' understanding of worship and its characteristics at Madrasah Aliyah Guppi Rannaloe. This study uses a quantitative approach with pre-test and post-test methods to measure changes in students' understanding before and after the implementation of the learning model. In addition, observations and interviews were used to obtain data on student participation and involvement during the learning process. The results showed that the implementation of the Quantum Teaching model significantly improved students' understanding of worship material. In the first cycle, students showed a significant increase in their knowledge of the requirements and pillars of worship, as well as the importance of intention in worship. The use of various interactive methods, such as group discussions, role plays, and the use of multimedia, also increased students' interest and motivation in learning. The second cycle showed better results, with more intensive use of technology and multimedia aids. Students were more active in participating in discussions and were able to relate worship material to everyday life. This improvement was increasingly seen in the third cycle, where students not only understood the rituals of worship but also applied the moral values ​​contained in worship, such as patience, humility, and gratitude. Based on these findings, it can be concluded that the Quantum Teaching learning model is effective in improving students' understanding of worship and its characteristics. The application of a student-centered approach, the use of technology, and reflective activities have been proven to increase student engagement and deepen their understanding of the teaching material. Therefore, this model is highly recommended for application in religious education to create a more meaningful and effective learning experience.